Utilization of Mangrove Forest on Curiak Island - Rizal, Muhammad Khairul; Abbas, Ersis Warmansyah; Handy, Muhammad Rezky Noor; Syarifuddin, Syarifuddin; Triyono, Sigit; Sari, Raihanah (Journal of Social Development, 2024)
Mangroves are typical coastal ecosystems and swampy areas that are influenced by tides. The forest around Curiak Island plays an important role. One of the benefits of mangrove forests is as a habitat for flora and fauna in them. The mangrove forest of Curiak Island is home to wildlife such as the presence of Proboscis monkeys that live in mangrove forests. The purpose of this study is (1) To describe what are the benefits of mangrove forests on Curiak Island, by knowing the benefits provided by mangrove trees, the community is expected to maintain the preservation of mangrove forests on Curiak Island by not damaging them. (2) To determine the integration of the use of mangrove forests on Curiak Island as a source of social studies learning This study uses qualitative descriptive methods, the application of this research method aims to facilitate researchers in assessing various community activities that want to be studied. The data collection technique carried out is observation to the exact research location on Curiak Island and conducting interviews with the surrounding community, SBI Foundation, Anjir Muara Sub-district to teachers and lecturers related to integrating the title and results of research with social studies learning materials so that this research can be a source of social studies learning. Conclusions on the research on the use of mangrove forests on Curiak Island, the benefits that can be utilized by the community and flora and fauna ecosystems whose areas are managed by the SBI Foundation, the community and Anjir Muara Village officials, the use of mangrove forests found are: 1.) As a proboscis monkey habitat. 2) Increase economic resources. 3.) River water wave barrier. 4.) As a folk remedy. 5.) Mangroves as building materials. 6.) Improve air quality.   this is in accordance with the use of mangrove forests on Curiak Island as a social studies learning resource related to grade 7 social studies learning materials